Clinical Pattern and Spectrum of Atypical Endometriosis: A Series of 5 Cases - Shirazi, Nadia; Nautiyal, Ruchira; Jindal, Rashmi (International Journal of Innovative Research in Medical Science, 2023)
Endometriosis refers to the extrauterine presence of hormonally active endometrial glands and stroma. This ectopic endometrial tissue exhibits cyclic bleeding, inflammation, fibrosis and leads to formation of adhesions. Endometriosis affects about 10% to 15% of women between 15 to 45 years of age. Clinical presentations vary from infertility, dysmenorrhoea, chronic pelvic pain, deep dyspareunia and even bleeding at external sites like the umbilicus. Besides involving fallopian tubes, bowel, liver, thorax, pericardium, pleura etc, the most commonly affected areas in the gastrointestinal tract are the descending colon, rectosigmoid, appendix, and ileo-caecum in descending order of frequency. This case series highlights some unusual presentations of endometriosis along with co-existence of other ovarian pathologies which are not frequently encountered in clinical practice. This series also highlights the role of preoperative radiology for an adequate clinical diagnosis and complete surgical excision.